Structural, morphological and rheological characterisation of bovine serum albumin–cress seed gum complex coacervate. (4th May 2022) - Hamedi, Fatemeh; Razavi, Seyed Mohammad Ali; Sharif, Ali
Summary: The interactions between the bovine serum albumin (BSA) and cress seed gum (CSG) were investigated by structural, morphological and rheological characterisation as a function of pH level (7.0–2.0) and biopolymers' concentrations (BSA, 0.1%, 0.5% and 1%, w/w and CSG, 0.01%, 0.05% and 0.1%, w/w). The results showed that turbidity, zeta potential and coacervate yield values had correlations with the initial number of biopolymers, which are influenced by the level of the positive and negative charges of BSA and CSG. Furthermore, the optimal complexation conditions in terms of pH, CSG‐BSA content and yield were 3.5%, 0.05–0.1% and 61.17% respectively. Rheological properties revealed the formation of a weakly gel‐like structure with a shear‐thinning behaviour. X‐ray diffraction (XRD) and scanning electron microscopy (SEM) authenticated an amorphous and branch‐like network structure in the coacervate phase respectively. These results reflect that CSG‐BSA complex coacervate could be an appropriate biopolymer carrier for susceptible and bioactive compounds. Abstract : Characterisation of bovine serum albumin‐cress seed gum complex coacervate.